2020
DOI: 10.48107/cmj.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Dental Anxiety Among University Students And Affect On Dental Attendance

Abstract: Objective: To investigate the prevalence of dental anxiety in an adult Caribbean population and explore its relationship to socio-demographic factors and dental attendance. Methods: An anonymous self-administered questionnaire was distributed to students attending The University of The West Indies, in Trinidad. The questionnaire included demographic items, self-rated oral health and dental attendance and the Modified Dental Anxiety Scale (MDAS). This self-reported instrument has five questions about anxiety t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…Our study found a statistically significant inverse relationship: higher levels of education correlated with lower levels of dental anxiety. This contrasts with a Pakistani study, which found that higher levels of education were associated with increased dental anxiety (SIRAJ et al 2020), while a Caribbean study found no significant effect of education on dental anxiety (REID et al 2020). The contextual nature of this relationship becomes clear when specific educational settings are examined.…”
Section: Educationcontrasting
confidence: 58%
“…Our study found a statistically significant inverse relationship: higher levels of education correlated with lower levels of dental anxiety. This contrasts with a Pakistani study, which found that higher levels of education were associated with increased dental anxiety (SIRAJ et al 2020), while a Caribbean study found no significant effect of education on dental anxiety (REID et al 2020). The contextual nature of this relationship becomes clear when specific educational settings are examined.…”
Section: Educationcontrasting
confidence: 58%